A STUDY OF INVENTORY CONTROL TECHNIQUES TO OPTIMISE REVENUE IN SMALL RETAIL STORES (Journal of Pharmaceutical Negative Results, 2022)
According to an estimation, there were around 12.65 million retail grocery stores in India in 2020. These Stores typically covered 100-200 square feet and kept stock of around 500-1000 items. These small retail shops generate yearly average revenue of 18-25 lac, of this the profit margins are around 3-4% i.e., Rs 54,000-72,000 yearly. From discussions with shop owners running small to medium retail stores from two-three generations, the challenge seems to be either overstocking leading to wastage, or stock-out leading to customer diversion. Small retail stores usually are managed using the primitive hit and trial method when it comes to inventory management, that only becomes moderately efficient in case of extensive experience of the manager. The following paper presents a study of three inventory control techniques in order to optimize revenue by controlling the inventory efficiently for small retail stores in India. The purpose of this study is to figure out a pattern connecting inventory control with optimal revenue which may further be converted into an algorithm for software that may help small retail store owners all over India.